Internship Reports and monograph "Population pharmacokinetic analysis of levetiracetam based on plasma or saliva therapeutic monitoring" - Fialho, Miguel José Correia (2023)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia